Characteristics of patients aged over 75 years with hepatitis C virus infection treated with direct‐acting antivirals in Japan: Evidence based on the nationwide, real‐world database in Japan. Issue 4 (1st March 2021) - Masaki, Naohiko; Kawasaki, Youhei; Nozaki, Yuichi; Yanase, Mikio
Abstract: Aim: Direct‐acting antivirals (DAAs) have dramatically changed the treatment of chronic hepatitis C. Their high efficacy helps in eradicating hepatitis C virus with few adverse events. Information on real‐world use of DAAs therapy in patients aged 75 years and older is inadequate. Methods: The Japanese DAAs database was constructed in 2014 as a cooperative system between 18 prefectures. The medical reports filled in by doctors and anonymized at the local government office were collected. The patients' demographic features, viral factors, and treatment characteristics were compared among three groups stratified by age when therapy was initiated: Group A (<60 years old), Group B (60–74 years old), and Group C (≥75 years old). Results: Out of the 22, 454 patients whose age upon starting therapy could be identified, 24.8% ( n = 5597) belonged to Group C, which was ten times the number in the Japanese Interferon Database. Female patients, advanced stages of liver fibrosis, and past history of hepatocellular carcinoma treatment were significantly higher in the older age groups (Group A < B < C), whereas sustained virologic response (SVR) rates were not different (91%–93%). In Group C, multivariate logistic regression analysis revealed that predicting factors for virologic response varied among DAAs regimens. However, the completion of DAAs therapy commonly contributed to SVR, regardless of DAAs regimen. Conclusions: DAAs therapy is associated with high SVR rates, even in the oldest age group, and therapy should not be withheld on the basis of old age.